Aggregation‐Induced Emission Gold Clustoluminogens for Enhanced Low‐Dose X‐ray‐Induced Photodynamic Therapy. Issue 25 (5th September 2019) - Sun, Wenjing; Luo, Li; Feng, Yushuo; Cai, Yuting; Zhuang, Yixi; Xie, Rong‐Jun; Chen, Xiaoyuan; Chen, Hongmin
Abstract: The use of gold nanoparticles as radiosensitizers is an effective way to boost the killing efficacy of radiotherapy while drastically limiting the received dose and reducing the possible damage to normal tissues. Herein, we designed aggregation‐induced emission gold clustoluminogens (AIE‐Au) to achieve efficient low‐dose X‐ray‐induced photodynamic therapy (X‐PDT) with negligible side effects. The aggregates of glutathione‐protected gold clusters (GCs) assembled through a cationic polymer enhanced the X‐ray‐excited luminescence by 5.2‐fold. Under low‐dose X‐ray irradiation, AIE‐Au strongly absorbed X‐rays and efficiently generated hydroxyl radicals, which enhanced the radiotherapy effect. Additionally, X‐ray‐induced luminescence excited the conjugated photosensitizers, resulting in a PDT effect. The in vitro and in vivo experiments demonstrated that AIE‐Au effectively triggered the generation of reactive oxygen species with an order‐of‐magnitude reduction in the X‐ray dose, enabling highly effective cancer treatment. Abstract : Cancer‐killing clusters : Aggregation‐induced emission gold clustoluminogens (AIE‐Au) for X‐ray‐induced photodynamic therapy (X‐PDT) were designed. Under low‐dose X‐ray irradiation, AIE‐Au strongly absorbed X‐rays and efficiently generated hydroxyl radicals, which enhanced the radiotherapy effect. Additionally, AIE‐AuX‐ray‐induced luminescence excited the conjugated photosensitizers, resulting in a PDT effect.